2018
DOI: 10.1002/cam4.1396
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 mutation and its prognostic significance in Chinese chronic lymphocytic leukemia: a retrospective study of 317 cases

Abstract: The proto‐oncogene NOTCH1 is frequently mutated in around 10% of patients with chronic lymphocytic leukemia (CLL). This study analyzed NOTCH1 mutation status of 317 Chinese patients with CLL by Sanger sequencing. The frequencies of NOTCH1 mutation in the PEST (proline (P), glutamic acid (E), serine (S), threonine (T)‐rich protein sequence) domain and the 3′ untranslated regions (UTR) were 8.2% and 0.9%, with the most frequent mutation being c.7541_7542delCT and c.*371A>G, respectively. Clinical and biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Also, according to the relationship between UM‐IgV H with naive B‐cells and increased survival of CLL cells through activation of BCR, it appears that CLL patients with UM‐IgV H compared with CLL patients with M‐IgV H can be associated with shorter survival, resistance to therapy, and progression of disease (Mougalian & O'Brien, ; Shahjahani et al, ). In addition, studies have indicated a relationship between UM‐IgV H with poor prognostic factors such as zeta chain‐linked protein 70 (ZAP‐70) and CD38 (Figure ; Doubek et al, ; Kröber et al, ), as well as high‐risk genomic aberrations such as deletion (del) 11q, del 17p, neurogenic locus notch homolog 1 (Notch1) mutations and trisomy 12, while M‐IgV H has only been reported that has relationship with del 13q (Athanasiadou et al, ; Rigolin et al, ; Sandoval‐Sus et al, ; Zou et al, ). Considering the above statements, it can be concluded that the evaluation of IgV H mutational status in B‐cells can have an important role in predicting the pathogenesis of CLL patients.…”
Section: Expression Alteration Of B‐cell CD Markers In Cllmentioning
confidence: 99%
“…Also, according to the relationship between UM‐IgV H with naive B‐cells and increased survival of CLL cells through activation of BCR, it appears that CLL patients with UM‐IgV H compared with CLL patients with M‐IgV H can be associated with shorter survival, resistance to therapy, and progression of disease (Mougalian & O'Brien, ; Shahjahani et al, ). In addition, studies have indicated a relationship between UM‐IgV H with poor prognostic factors such as zeta chain‐linked protein 70 (ZAP‐70) and CD38 (Figure ; Doubek et al, ; Kröber et al, ), as well as high‐risk genomic aberrations such as deletion (del) 11q, del 17p, neurogenic locus notch homolog 1 (Notch1) mutations and trisomy 12, while M‐IgV H has only been reported that has relationship with del 13q (Athanasiadou et al, ; Rigolin et al, ; Sandoval‐Sus et al, ; Zou et al, ). Considering the above statements, it can be concluded that the evaluation of IgV H mutational status in B‐cells can have an important role in predicting the pathogenesis of CLL patients.…”
Section: Expression Alteration Of B‐cell CD Markers In Cllmentioning
confidence: 99%
“…NOTCH1 mutation is one of the most essential molecular biological aberrations in CLL [2] . In the era of chemo-immunotherapy, patients with NOTCH1 mutation showed a poor response to treatment and had an adverse prognosis [19] . In addition, NOTCH1 and B cell receptor signals could support each other to promote the development of CLL.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In the era of chemo-immunotherapy, patients with NOTCH1 mutation showed a poor response to treatment and had an adverse prognosis. [ 19 ] In addition, NOTCH1 and B cell receptor signals could support each other to promote the development of CLL. NOTCH1 mutation enhanced the expression of the B cell receptor signal by activating the NOTCH1 pathway, which in turn facilitated the translation and activation of the NOTCH1 signal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients carrying these mutations had a more advanced stage of CLL and a higher risk of undergoing transformation into diffuse large B-cell lymphoma (DLBCL) than patients with CLL without genetic changes. Notch 1 mutations in CLL patients seem to be useful as a predictive risk factor of malignancy evolution [ 77 , 78 , 79 , 80 ].…”
Section: Notchmentioning
confidence: 99%